FEEDING HABITS OF INTRODUCED INVASIVE SPECIES PIKEPERCH SANDER LUCIOPERCA (LINNE, 1758) IN THE RESERVOIR OF GHRIB DAM (NORTHWEST ALGERIA) - Billel Belaifa1,*, Amina Bouamra1, Yasmine I. Arab1, Mohamed H. Kara2, and Abdeslem Arab1 (Chelonian Research Foundation, 2024)
When an introduced fish species successfully adapts to new ecological conditions, they significantly reduce the number of indigenous species. This paper aims to determine impacts that introduction of invasive species Sander lucioperca (Linnaeus 1758) has on native fish species in the reservoir of Ghrib dam (western Algeria). The diet of the introduced pikeperch was studied from September 2020 to August 2021. Trophic activity was assessed using the digestive vacuity coefficient (Cv). The index of relative importance (IRI), which combines frequency of occurrence (F), the number (Cn), and restored weight (Cp) of different ingested prey, was used to characterize the relative importance of different food taxa. Qualitative and quantitative variations in diet were studied according to pikeperch size (small, medium and large) and season. In total, 193 stomachs were empty, corresponding to a digestive vacuity coefficient of 44.47%. Qualitative study of stomach contents indicates that this species is omnivorous, with an ichtyophage trend. Three groups of prey were identified: Amphipodan (IRI = 1.03; Gammarus sp.), Dipteran (IRI = 4.73; Chironomus sp.) and primarily fishes (IRI = 94.24; Cyprinus carpio, Rutilus rutilus, and Sander lucioperca). Significant differences in feeding habits occur according to season and pikeperch size, showing also, the risk of cannibalism was highest among the largest pikeperch. KEY WORDS: - Feeding habits, Predation pressure, Sander lucioperca, The Index (IRI), The reservoir of Ghrib dam.